Scrutinizing the Political and Economic Dynamics of China's Distribution of Vaccines in Securitizing Health - Christou Imanuel Siregar; Theo Gerald Napitupulu (Institute of International Studies, 2020)
In the previous Pandemic of the H5N1 virus, the world is facing an uneven distribution of the vaccine. The irony is that developed countries get more access to vaccines compared to the country with more cases especially the global south countries. Today, the world is facing another pandemic which is The Covid-19 Pandemic. This virus vaccine has been found by Russia but has not yet gained international trust. According to experts, China is the country with the most potential to produce this vaccine. However, after the vaccine is successfully produced, there is no assurance that the vaccine will evenly be distributed as mandated by WHO. Based on these considerations, the researcher aimed to project the possibilities of vaccine distribution from China to global south countries. Researchers want to analyze the influence of a country's economic capacity and international politics on vaccine distribution, especially with China. To achieve this objective, we will compare the political and economic situation during the H5N1 pandemic and the political and economic situation during the Covid-19 pandemic. Countries used for comparison are Kenya, Yemen, the Philippines, and Indonesia. These four countries were chosen because it could represent different conditions of political and economic relations. The expected result is that we will get an overview of the distribution of the Covid-19 vaccine when China has started the distribution of the vaccine. We hope that this paper can be a consideration for developing countries' governments to be more sensitive and intense in carrying out vaccine diplomacy.